DOI: 10.11606/d.75.2007.tde-25102007-165457
|View full text |Cite
|
Sign up to set email alerts
|

Utilização de polianilina como revestimento protetor contra corrosão das ligas de alumínio 2014 F, 2024 T3 e 7075 O

Abstract: Aluminum is widely used due to its technical and economic advantages, as well as due to its high level of corrosion protection provided by the oxide film formed on the surface of the metal. In the current study deposition of polyaniline (PAni) on three different Al alloys (AA-2014 F, AA-2024 T3 and 7075 O) was studied. The electrodepositions were

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 25 publications
(32 reference statements)
0
2
0
Order By: Relevance
“…In this way, the use of protective coatings appears as a possible alternative against the advancement of the corrosion process of the AA2524-T3 alloy. In this context, chromatization is the most effective conversion coating for Al-alloys 22 . However, the tailings from the treatment process are highly toxic, which makes their use unfeasible 22 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this way, the use of protective coatings appears as a possible alternative against the advancement of the corrosion process of the AA2524-T3 alloy. In this context, chromatization is the most effective conversion coating for Al-alloys 22 . However, the tailings from the treatment process are highly toxic, which makes their use unfeasible 22 .…”
Section: Introductionmentioning
confidence: 99%
“…In this context, chromatization is the most effective conversion coating for Al-alloys 22 . However, the tailings from the treatment process are highly toxic, which makes their use unfeasible 22 . Several reports have shown that conductive polymers can be useful in corrosion protection as a form of coating onto metals and metal alloys by using electrochemical deposition techniques 5,[23][24] .…”
Section: Introductionmentioning
confidence: 99%